Poisoning of mice by Baccharis coridifolia: An experimental model - Varaschin, Mary Suzan [UNESP]; Alessi, Antonio Carlos [UNESP] (My University, 2003)
The poisonous plant Baccharis coridifotia causes necrosis in lymphoid tissues and the gastrointestinal tract of cattle, horses, sheep and rabbits. An experimental poisoning of mice was undertaken to establish an experimental model in a laboratory animal specie. A single 5 to 8-g/kg dose of a suspension of the plant was administered by gavage to II mice. To 3 other control mice, the same volume of water was administered. Plant-dosed mice manifested clinical effects after 12 h: tachipnea, trembles, dehydration and prostration. Most of the dosed mice died 14 to 33 h after plant administration-3 survived for 12 d. Six mice had remarkable necrosis of the germinative center of secondary follicles in lymph nodes and spleen; 3 mice had necrosis of lymphoid tissues in intestine and thymus. Mice reproduce most of the lesions observed in naturally poisoned cattle and the use of this specie as an experimental model is valid.
Keywords: animal experiment; animal model; Baccharis cordifolia; cattle; controlled study; dehydration; female; gastrointestinal tract; horse; lymphoid tissue; male; mouse; nonhuman; plant; plant intoxication; rabbit; sheep; tachypnea; tissue necrosis; Administration, Oral; Animals; Baccharis; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Liver; Lymph Nodes; Male; Mice; Plant Poisoning; Plants, Toxic; Poisoning; Spleen; Animalia; Bos taurus; Equidae; Equus caballus; Oryctolagus cuniculus; Ovis aries